VD_FINDINFO HC / 2014 / 414 vom 7. Mai 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, ENFANT NÉ HORS MARIAGE, SUBROGATION DE LA COLLECTIVITÉ PUBLIQUE | 276 al. 1 CC, 286 al. 2 CC, 289 al. 2 CC